A reflection on the use of semi-structured interviews - Dearnley, Christine (Nurse researcher, 2005)
Based on the her experiences of completing a doctoral study in which semi-structured interviews featured as the primary data collection method, Christine Dearnley offers a reflective insight into using semi-structured interviews as a method of data collection. The processes of reflection in, and on, the interview process are explored, and some of the ethical dilemmas that emerged during the study are reflected on. The practicalities of conducting semi-structured interviews are considered with a view to sharing new understandings of the process and its management.